STYLISTIC DIFFERENTIATION OF THE ENGLISH VOCABULARY - Izzatov Fathulla; Akramova N. (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: The English vocabulary is characterized by a significant degree of stylistic differentiation, reflecting the diverse social, cultural, and communicative contexts in which the language is used. This study aims to explore the multifaceted nature of English vocabulary from a stylistic perspective, focusing on how different lexical items are selected depending on the formality of the situation, the speaker’s intention, and the target audience. The paper examines various stylistic layers, including formal, informal, colloquial, slang, jargon, and dialectal words. It also considers semantic nuances and connotations that affect the choice of vocabulary. Understanding stylistic differentiation is crucial for effective communication, as it helps speakers and writers tailor their language to suit specific contexts, avoid misunderstandings, and convey appropriate attitudes and emotions. The paper further discusses the role of sociolinguistic factors such as age, gender, profession, and regional background in shaping vocabulary choices. Finally, this study highlights the dynamic and evolving nature of English stylistic vocabulary in response to cultural and technological changes.